Hubungan Aspek Sosial Budaya Dengan Penggunaan Iud Pada Pasangan Usia Subur Di Wilayah Kerja Puskesmas Sungai Raya Kabupaten Aceh Timur Tahun 2021 - Br Hsb, Nova Radiani (Jurnal Maternitas Kebidanan, 2024)
IUDs are one of the modern contraceptives that have been designed in such a way placed in the uterine cavity as a contraceptive, blocking fertilization, and making it difficult for the egg to implement in the uterus. The purpose of this study was to find out the relationship between social and cultural aspects with the use of IUDs in fertile couples in the working area of ​​Sungai Raya Puskesmas Kabupaten Kabupaten Aceh Timur in 2021. The research design used in this study was an analytic survey with cross sectional design. The population of this study are all Pairs of Ages Fertile located in the Working Area of ​​Sungai Raya Puskesmas in 2021 which amounted to 1897 people. Sampling was done by using Slovin formula obtained by 95 samples by using random stratification technique. The study was conducted from 30 July to 5 August 2021by interview using questionnaire. Statistical test using chi-square test.The results showed that the majority of respondents did not use IUD that is as much as 63 respondents (66.3%). The majority of respondents with socio-cultural aspects that do not support that is as much as 64 respondents (67.4%). Statistically There is Relationship of Culture and Social Aspect with use of IUD to Pair Age in Working Area of ​​Health Center of Sungai Raya Regency of East Aceh Year 2021 with P Value 0.000. For FP acceptors it is expected to consider various contraceptive alternatives by comparing the side effects of long-term use of contraceptives in the future.